1998
DOI: 10.1172/jci1140
|View full text |Cite
|
Sign up to set email alerts
|

CTS1: a p53-derived chimeric tumor suppressor gene with enhanced in vitro apoptotic properties.

Abstract: The clinical potential of the p53 tumor suppressor gene is being evaluated currently for gene therapy of cancer. We have built a variant of wild-type p53, chimeric tumor suppressor 1 (CTS1), in which we have replaced the domains that mediate its inactivation. CTS1 presents some very interesting properties: (a) enhanced transcriptional activity; (b) resistance to the inactivation by oncogenic forms of p53; (c) resistance to the inactivation by MDM2; (d) lower sensitivity to E6-induced degradation; (e) ability t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 44 publications
0
30
0
2
Order By: Relevance
“…Several such p53 variants have been described, including p53(14/19) and p53(22/23) with amino acid substitutions in the MDM2 binding domain (16), p53(d 13 -19) with a deletion in the MDM2 binding site (15), and the chimeric p53 analogue CTS1 in which the entire NH 2 -terminal domain comprising the MDM2 binding site was replaced by the herpes simplex virus VP16 transactivation domain (21). The variants p53(14/19), p53(d 13 -19), and CTS1 have already been introduced into cancer cells with high MDM2 expression by means of replication-deficient adenovirus vectors and shown to confer growth inhibition and apoptosis induction in these cells (22 -25).…”
Section: Resultsmentioning
confidence: 99%
“…Several such p53 variants have been described, including p53(14/19) and p53(22/23) with amino acid substitutions in the MDM2 binding domain (16), p53(d 13 -19) with a deletion in the MDM2 binding site (15), and the chimeric p53 analogue CTS1 in which the entire NH 2 -terminal domain comprising the MDM2 binding site was replaced by the herpes simplex virus VP16 transactivation domain (21). The variants p53(14/19), p53(d 13 -19), and CTS1 have already been introduced into cancer cells with high MDM2 expression by means of replication-deficient adenovirus vectors and shown to confer growth inhibition and apoptosis induction in these cells (22 -25).…”
Section: Resultsmentioning
confidence: 99%
“…To explore this possibility, we compared inhibition of colony formation by p53 with CTS1, a chimeric p53 molecule (Conseiller et al, 1998). CTS1 is resistant to inactivation by MDM2 since it has the VP16 activation domain in the place of the p53 activation domain that interacts with MDM2.…”
Section: Tumour Cell Linesmentioning
confidence: 99%
“…3 We previously reported that Ad-CTS-1 kills human gliomas independent of their endogenous p53 status and more efficiently than wild-type p53. The biochemical pathways mediating CTS-1-induced cell death remained obscure, but did not involve death ligand/receptor interactions, caspase activation or altered BCL-2 family protein expression.…”
Section: Discussionmentioning
confidence: 98%
“…The carboxyterminal self-inhibitory domain of p53 is deleted. 3 Adenoviral CTS-1 gene transfer induces growth arrest and loss of viability in p53 wild-type and p53 mutant human malignant cell lines better than wildtype p53 4 as well as in mouse-double-minute-2 (MDM-2)-overexpressing breast cancer cells. 5 Since the best-established function of p53 is to act as a transcription factor regulating the expression of genes involved in growth inhibition, DNA repair and apoptosis, we here assessed whether specific differences in the modulation of gene expression are responsible for the superior antitumor properties of CTS-1 compared with wild-type p53 using cDNA microarray analysis.…”
Section: Introductionmentioning
confidence: 99%